2017
DOI: 10.1080/07399332.2017.1326921
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating female nursing students' knowledge and attitudes regarding breast self-examination

Abstract: The purpose of this study was to evaluate female nursing students' knowledge and attitudes regarding breast self-examination (BSE). The sample consisted of 175 nursing students from a university in Cyprus. We collected data via a questionnaire that included the Greek version of the Champion Health Belief Model scale and questions regarding the participants' demographic characteristics. More than half of the participants (58.3%) said that they were knowledgeable about BSE and 29.1% of them had been taught about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
6
2
2
Order By: Relevance
“…In our logistic regression analysis, it was determined that the BSE rate increased as the confidence / self-efficacy score increased. Spountzi-Krepia et al, Aker at al., Lee, and Lavdaniti showed that the ratio of BSE increased as trust/self efficiacy increased in logistic regression models [13,15,18,21]. Although, the CHBMS perceived barriers subscale was found to be significant in univariate analysis in our study, it was found that regular regression model did not significantly affect BSE performance.…”
Section: Original Articlecontrasting
confidence: 73%
See 1 more Smart Citation
“…In our logistic regression analysis, it was determined that the BSE rate increased as the confidence / self-efficacy score increased. Spountzi-Krepia et al, Aker at al., Lee, and Lavdaniti showed that the ratio of BSE increased as trust/self efficiacy increased in logistic regression models [13,15,18,21]. Although, the CHBMS perceived barriers subscale was found to be significant in univariate analysis in our study, it was found that regular regression model did not significantly affect BSE performance.…”
Section: Original Articlecontrasting
confidence: 73%
“…Sapountzi-Krepia et al, also found that the ratio of nursing students in Cyprus who performed regular BSE for more than a year as 10.9% [13]. Besides, in 2014 Health Statistics Yearbook, published by Turkish Ministry of Health, it was reported that 10.1% of women regularly performed BSE every month [4].…”
Section: Original Articlementioning
confidence: 99%
“…Segni ve arkadaşları [18] ortalama yaşları 22,9 yıl olan üniversite öğrencisinden oluşan 368 olguyu inceledikleri çalışmada, KKMM'nin uygulanma oranını düşük bulmuş (%44,2), bunun nedenlerini öğrencilerin KKMM'nin nasıl yapıl-dığını bilmemeleri ve kendilerini sağlıklı görmeleri olarak belirtmişlerdir. Krepia ve arkadaşlarının [19] toplamda 175 hemşirelik öğrencisinin bilgi ve tutumlarını inceledikleri çalışmalarında, öğrencilerin sadece %10'unun periyodik olarak KKMM yaptığı ve bu öğrencilerde uygulamaya iliş-kin ciddiyet ve yarar algısının yüksek çıktığı saptanmıştır.…”
Section: Discussionunclassified
“…In the literature, no publication was found on performing BSE by nurses and their preparation to prevention of breast cancer in Europe. Only one paper on BSE by nursing students in Cyprus [44] was found.…”
Section: Introductionmentioning
confidence: 99%